(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Supernumerary teeth are defined as excess number of teeth as compared to normal dental formula. Mesiodens is a supernumerary tooth in the central region of premaxilla between two central incisors. Multiple Mesiodens are called Mesiodentes. This additional tooth structure may cause disturbance in eruption or position of adjacent teeth. Dens Invaginatus (DI) is a rare tooth malformation showing an infolding of enamel and dentin of affected tooth sometimes extending deep into the pulp cavity and root portion. This paper aims to present a rare association of DI in two of the four impacted Mesiodentes in a 10-year-old girl patient causing eruption disturbance and unaesthetic appearance in anterior maxilla.